Single-cell protein activity analysis reveals a novel subpopulation of chondrocytes and the corresponding key master regulator proteins associated with anti-senescence and OA progression - Guang, Zhao; Min, Zhang; Jun-Tan, Li; Tian-Xu, Dou; Xiang, Gao (Frontiers in Immunology, 2023)
Background: Osteoarthritis (OA) is a prevalent senescence-related disease with substantial joint pain, loss of joint function, and cartilage degeneration. Because of the paucity of single-cell studies of OA and the gene dropout problem of single-cell RNA sequencing, it is difficult to acquire an in-depth understanding of the molecular characteristics of various chondrocyte clusters. Methods: Here, we aimed to provide new insights into chondrocyte senescence and a rationale for the development of effective intervention strategies for OA by using published single-cell RNA-sequencing data sets and the metaVIPER algorithm (Virtual Inference of Protein activity by Enriched Regulon). This algorithm was employed to present a proteome catalog of 62,449 chondrocytes from the cartilage of healthy individuals and OA patients at single-cell resolution. Furthermore, histopathologic analysis was carried out in cartilage samples from clinical patients and experimental mouse models of OA to validate above results. Results: We identified 16 protein-activity-based chondrocyte clusters as well as the underlying master regulators in each cluster. By assessing the enrichment score of each cluster in bulk RNA-sequencing data, followed by gene-set variation analysis, we preliminarily identified a novel subpopulation of chondrocytes (cluster 3). This clinically relevant cluster was predicted to be the main chondrocyte cluster responsible for maintaining cellular homeostasis and anti-senescence. Specifically, we uncovered a set of the key leading-edge proteins of cluster 3 by validating the robustness of the above results using another human chondrocyte single-cell RNA-sequencing data set, consisting of 24,675 chondrocytes. Furthermore, cartilage samples from clinical patients and experimental mouse models of OA were used to evaluate the expression patterns of these leading-edge proteins, and the results indicated that NDRG2, TSPYL2, and HMGB2 are closely associated with OA pathogenesis and might play critical roles in modulating cellular homeostasis and anti-senescence in chondrocytes. Conclusion: Our study revealed a novel subpopulation of chondrocytes that are critical for anti-progression of OA and the corresponding master regulator proteins, which might serve as therapeutic targets in OA.